Socratic, Platonic and Aristotelian studies essays in honor of Gerasimos Santas - Anagnostopoulos, Georgios (Springer Netherlands, 2011)
This volume contains outstanding studies by some of the best scholars in ancient Greek Philosophy on key topics in Socratic, Platonic, and Aristotelian thought. These studies provide rigorous analyses of arguments and texts and often advance original interpretations. The essays in the volume range over a number of central themes in ancient philosophy, such as Socratic and Platonic conceptions of philosophical method; the Socratic paradoxes; Plato's view on justice; the nature of Platonic Forms, especially the Form of the Good; Aristotle's views on the faculties of the soul; Aristotle's functionalist account of the human good; Socratic, Platonic, and Aristotelian views on the nature of desire and its object. The volume will be of interest to students and scholars of ancient philosophy and classics.